Examining Climate Policy-Making Through a Critical Model of Evidence Use - Tangney, Peter (Frontiers in Climate, 2022)
Evidence-based decision-making has a been a focus of academic scholarship and debate for many decades. The advent of global, complex problems like climate change, however, has focused the efforts of a broader pool of scholarship on this endeavour than ever before. The ‘linear model’ of expertise, despite obvious problems, continues to be a touchstone for many policy practitioners as well as for academic understandings of evidence development and use. Knowledge co-production, by contrast, is increasingly proposed as both the antithesis and the solution to the linear model’s difficulties. In this paper I argue that, appropriately considered, both models have their uses for understanding evidence for policy, yet neither adequately accounts for the political contexts in which expert knowledge has often been asserted to address climate change. The paper proposes that the difficulty with both models lies in lingering assumptions about the information value of evidence for decision-making, the sensitivity of decision-making to scientific expertise, and the assumed mendacity or irrationality of decision-makers when they seem to fail to heed expert advice. This paper presents a model of evidence use that incorporates the aspirations of linear and co-production frameworks, while providing appropriate guidance for evaluating the role of expert knowledge in climate change policy-making.